Lifetime risk of comorbidity in patients with simple congenital heart disease: a Danish nationwide study. (7th December 2022) - El-Chouli, Mohamad; Meddis, Alessandra; Christensen, Daniel M; Gerds, Thomas A; Sehested, Thomas; Malmborg, Morten; Phelps, Matthew; Bang, Casper N; Ahlehoff, Ole; Torp-Pedersen, Christian; Sindet-Pedersen, Caroline; Raunsø, Jakob; et al.
Abstract: Aims: In a continuously ageing population of patients with congenital heart disease (CHD), understanding the long-term risk of morbidity is crucial. The aim of this study was to compare the lifetime risks of developing comorbidities in patients with simple CHD and matched controls. Methods and results: Using the Danish nationwide registers spanning from 1977 to 2018, simple CHD cases were defined as isolated atrial septal defect (ASD), ventricular septal defect (VSD), pulmonary stenosis, or patent ductus arteriosus in patients surviving until at least 5 years of age. There were 10 controls identified per case. Reported were absolute lifetime risks and lifetime risk differences (between patients with simple CHD and controls) of incident comorbidities stratified by groups and specific cardiovascular comorbidities. Of the included 17 157 individuals with simple CHD, the largest subgroups were ASD (37.7%) and VSD (33.9%), and 52% were females. The median follow-up time for patients with CHD was 21.2 years (interquartile range: 9.4–39.0) and for controls, 19.8 years (9.0–37.0). The lifetime risks for the investigated comorbidities were higher and appeared overall at younger ages for simple CHD compared with controls, except for neoplasms and chronic kidney disease. The lifetime risk difference among the comorbidity groups was highest for neurological disease (male: 15.2%, female: 11.3%), pulmonary disease (male: 9.1%, female: 11.7%), and among the specific comorbidities for stroke (male: 18.9%, female: 11.4%). The overall risk of stroke in patients with simple CHD was mainly driven by ASD (male: 28.9%, female: 17.5%), while the risks of myocardial infarction and heart failure were driven by VSD. The associated lifetime risks of stroke, myocardial infarction, and heart failure in both sexes were smaller in invasively treated patients compared with untreated patients with simple CHD. Conclusion: Patients with simple CHD had increased lifetime risks of all comorbidities compared with matched controls, except for neoplasms and chronic kidney disease. These findings highlight the need for increased attention towards early management of comorbidity risk factors. Structured Graphical Abstract: Structured Graphical Abstract Background, methods, and highlighted results of the current study investigating the lifetime risks of comorbidities and mortality in patients with simple congenital heart disease compared with sex- and birth-year-matched controls. 'Excess risk' means the excess risk among simple congenital heart disease patients compared with sex- and birth-year-matched controls. CHD, congenital heart disease.